2003
DOI: 10.1097/00004703-200312000-00002
|View full text |Cite
|
Sign up to set email alerts
|

How Do Primary Care Physicians Identify Young Children with Developmental Delays? A National Survey

Abstract: Little is known about the current practices of primary care physicians regarding developmental surveillance and screening during pediatric preventive care visits. We conducted a mailed survey of a random national sample of pediatricians and family physicians to describe their practices and identify factors that predict use of developmental screening tools, an efficacious way of identifying children with developmental delays. Most physicians reviewed developmental milestones and prompted parents for development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 23 publications
4
110
0
9
Order By: Relevance
“…A number of studies suggest that more physicians rely on clinical judgment or a few questions more than on standardized measures. [46][47][48][49][50] Unless validated measures are implemented in a reliable manner, it may be more effective for physicians to rely on parental concern as a measure of need. 51,52 Limitations A number of study limitations should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies suggest that more physicians rely on clinical judgment or a few questions more than on standardized measures. [46][47][48][49][50] Unless validated measures are implemented in a reliable manner, it may be more effective for physicians to rely on parental concern as a measure of need. 51,52 Limitations A number of study limitations should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Physician estimates of the developmental status of children are much less accurate when only clinical impressions, rather than formal screening tools, are used, 256,257 yet a minority of PCPs use formal developmental screening instruments, 258,259 and few pediatricians specifically screen for ASDs. 5 A standardized screening tool should be administered at any point when concerns about ASDs are raised spontaneously by a parent or as a result of clinician observations or surveillance questions about social, communicative, and play behaviors (Steps 5a and 5b).…”
Section: Screening For Asds (Steps 5a-5c)mentioning
confidence: 99%
“…This delay may be due to inadequate screening practices (Dearlove & Kearney, 1990;Dobos, Dworkin, & Bernstein, 1994;Sices, Feudtner, McLaughlin, Drotar, & Williams, 2003), pediatricians' slow response to parental concerns (Glascoe, 1997;Shevell, Majnemer, Rosenbaum, & Abrahamowicz, 2001), the low sensitivity of screening instruments for autism (Dumont-Mathieu & Fein, 2005), and a general lack of awareness of symptoms (Shah, 2001). Some researchers have suggested that the similarity of the features of autism with other disorders can lead to misdiagnosis Noterdaeme, Amorosa, Mildenberger, Sitter, & Minow, 2001;Ohta, Nagai, Hara, & Sasaki, 1987).…”
mentioning
confidence: 99%